Knowledge Management in Human Capital Development in the Context of the Digital Economy - N. Trenev, Vasiliy; ., . (International Journal of Engineering and Technology, 2018)
Modern market economy is marked by a high level of competition. Therefore, organizations have to dig for new development options to expand their economic potential and augment capital. Human capital – a stock of individual human capitals, as we define – can be one of such options. This article is a written discussion over mechanisms of transforming insider information into knowledge and intellectual capital. At this point, particular attention is paid to human capital development through the knowledge management problems, including factors that inhibit the effective use of human capital. This article also puts under discussion some of the requirements for the knowledge management system and its basic tasks.The Results section provides recommendations on gaining skills, knowledge and experience inside the organization. The action system of knowledge management is described.